Showing Agency on the Margins: African American Railway Workers in the South and Their Unions, 1917–1930 - Kelly, Joseph (Labour / Le Travail, 2013)
During World War I and the 1920s, African American trainmen throughout the South took advantage of federal administrative bodies that had set anti-discrimination rules to challenge racist employers and white trainmen alike. After the war, white workers insisted that African Americans be relegated to porter jobs. White employers demanded that African American workers who continued to work as brakemen and flagmen, as they had during the war, accept lower wages for such skilled work than their white counterparts were paid. The federal government preferred to turn a blind eye to racial discrimination against African American workers in the period after federal control of the railways ended. Despite this concerted attack from all sides on their rights, unions of African American trainmen continued their fight, with some success, before federal administrative tribunals as well as the courts to retain skilled positions and receive the same pay as their white equivalents. Only the devastation of rail jobs in the 1930s largely destroyed the African American trainmen’s wartime gains.